Oil and gas companies' ESG performance and firm value: impact of COVID-19 and the comparison between advanced economy and emerging market firms - Sia, Simon Seak Lung (2023)
Although there are extensive literatures that evaluate the ESG performance-firm financial performance (i.e., ESGP-FP) relationship, research on the ESGP-FP hyperlink among oil and gas companies (O&G) remain scarce. For practitioners especially oil firm managers, empirical work on ESG that account for the impacts of the recent COVID-19 pandemic and that also differentiate between advanced economy (AE) oil firms and emerging market (EM) oil firms are sorely lacking. This paper fills that gap.